The influence of precarious employment on career development: the current situation in Australia - Connell, Julia; Burgess, John (Emerald, 2006)
Purpose – The aim of this article is to explore the influence of precarious (temporary) employment on employability and career development. Design/methodology/approach – The article draws together primary and secondary research material. Findings – Findings indicate that there are both positive and negative perspectives with regard to temporary employment and career development for both the workers themselves and the user firms. Research limitations/implications – Implications arising are that policy development/research is required to investigate potential interventions that could be introduced. Practical implications – These are in line with the article's suggestion of adopting transitional labour market strategies. These major transitions are between education and employment; (unpaid) caring and employment; unemployment and employment; retirement and employment; “precarious” and permanent employment. Originality/value – The article outlines two facets of precariousness associated with temporary work in relation to the worker and the user firm. It also presents a newly devised three‐stage typology of skill and skill acquisition that is relevant to the topic.